The Role of Firm Size and Customer Orientation on Halal Transportation Adoption - Mohd Yunan, Yusrizal Sufardi; Ali, Mohd Helmi; Alam, Syed Shah (International Journal of Supply Chain Management, 2019)
The purpose of this paper is to propose an innovation adoption framework in the context of halal transportation. This paper provides a discussion on the development of halal transportation adoption framework using Technology-Organization-Environment (TOE) framework insight with literature. Currently, the issues on halal transportation adoption have still not been resolved even though several motivational factors have been identified to gain the attention from potential adopters. This paper further proposes innovation adoption factors for halal transportation. It consists of two internal organizational dimensions, namely: firm size and customer orientation. In addition, this paper also explains the roles that firm size and customer orientation can play on halal transportation adoption. Halal transportation adoption framework is important to halal logistics providers as it gives a significant input to the adoption of their services. Overall, this paper contributes to a newly-developed innovation adoption framework in the context of halal transportation.